Pengaruh Kepemimpinan Transformasional, Motivasi Dan Penempatan Terhadap Keterikatan Karyawan (Employee Engagement) Pegawai Generasi Y Dan Z KPP Pratama Kediri - Herlina Wahyuningtyas; Eka Askafi (Universitas Islam Kadiri, 2020)
This study aims to analyze the influence of transformational leadership on employee engagement, the influence of motivation on employee engagement and the influence of positioning on employee engagement. The type of research is descriptive quantitative with a questionnaire as the data source. The population used is the civil servant of Small Tax Service Office of Kediri that was birth in 1981 until 1990 (Y generation) and birth in 1991 until 2000 (Z generation) amounted to 50 people and sampling technique used saturated sample. Data analysis techniques used descriptive analysis. Data were analyzed using SPSS version 23 program. The results showed that transformational leadership had no significant effect on employee engagement, motivation had significant effect on employee engagement, positioning had no significant effect on employee engagement.